2002
DOI: 10.1177/0021998302036012163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stitching on In-Plane and Interlaminar Properties of Sisal/Epoxy Laminates

Abstract: The factors that influence in-plane mechanical responses and mode I interlaminar fracture toughness of stitched unidirectional sisal/epoxy laminates were studied in this paper. It was found that in-plane strength and stiffness of the laminates were not significantly affected by the stitching threads, while the interlaminar toughness was greatly improved, especially at higher sisal content. Unlike glass fiber reinforced polymer composites, sisal laminates have a rather high tolerance against the damages induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 11 publications
1
23
1
Order By: Relevance
“…To avoid flexural failure and torsion of the substrate beams of the double cantilever beam (DCB) specimens, a tabbed DCB (TDCB) configuration according to [17,22,52,53] was used to measure the mode I energy release rate of stitched and unstitched NCF laminates. A 25 lm thick fluorethylenpropylene (FEP) interlayer was inserted between the (B/2) NCFs (Fig.…”
Section: Mode I Energy Release Ratementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid flexural failure and torsion of the substrate beams of the double cantilever beam (DCB) specimens, a tabbed DCB (TDCB) configuration according to [17,22,52,53] was used to measure the mode I energy release rate of stitched and unstitched NCF laminates. A 25 lm thick fluorethylenpropylene (FEP) interlayer was inserted between the (B/2) NCFs (Fig.…”
Section: Mode I Energy Release Ratementioning
confidence: 99%
“…It was found that increased yarn diameters (denoted as yd) and stitch densities are usually correlated with enhanced CAI and G 1R data of the composite laminate. With regard to the fiber types used for structural stitching, carbon and aramid yarns reduce crack propagation much more than glass, polyester, polyamide or sisal yarns [9,15,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…But this may damage or at least change the microstructure of the fibers and usudoi: 10.1007/s11431-015-5911 -3 ally may introduce extra harmful chemical reagents such as coupling agents and alkali liquor in the process of operation. For laminated composites, some structural designing approaches can effectively improve interlaminar properties without the introduction of extra harmful reagents, such as z-pinning [10], stitching [11], 3D-weaving [12], etc. However, most of these techniques are costly or complicated in fabrication process and are normally with the penalty of the decrease in in-plane mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many researchers have reported obtaining well-intercalated structures when processing PBS with organo-modified clays such as C10A, C30B, MMT-LEA by either solvent casting, melt intercalation, or in situ polymerization Someya et al 2004;Shih et al 2007Shih et al , 2008Hwang et al 2009). Some authors have also reported the preparation of completely exfoliated PBS/clay nanocomposites by solvent casting (Shih et al 2007(Shih et al , 2008, melt intercalation , and in situ polymerization (Rong et al 2002) as well.…”
Section: Processing Of Biodegradable Clay Nanocompositesmentioning
confidence: 99%